Factors Associated with Depression in Elderly Patients with Hypertension - Lainsamputty, Ferdy; Laloan, Risty Mandane; Wu, Bo-Hsun (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Depression in elderly individuals with hypertension is a common but often underdiagnosed mental health issue that affects quality of life and treatment adherence. This study aimed to identify factors associated with depression in elderly patients with hypertension. Design : A descriptive correlational study with a cross-sectional design was conducted. Methods : This study involved 68 community-dwelling elderly patients with hypertension in a village of North Sulawesi selected through total sampling. Data were collected using structured questionnaires covering sociodemographic and clinical characteristics and the Geriatric Depression Scale-15 (GDS-15). Data were analyzed using the Mann-Whitney U test, Kruskal-Wallis H test, and Spearman’s rank correlation. Results : The mean depression score was 9.43 (SD = 1.79), with nearly half of participants experiencing moderate depression (48.5%). Only the duration of hypertension was significantly correlated with depression score (r = 0.275, p = 0.023). Conclusions : These findings highlight the need for routine depression screening among elderly hypertensive patients, particularly those with a longer history of illness. Clinical implications include adopting integrated care models that combine hypertension management with psychosocial support in primary care settings